Complete Heart Block Associated with Hepatitis A Infection in a Female Child with Fatal Outcome - Haseena Naseer (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Hepatitis A virus (HAV), a positive-strand RNA virus of the picornaviridae family, primarily spreads through the fecal-oral route, often via contaminated food. While most children are asymptomatic, 80% of exposed adults develop clinical symptoms like fever, jaundice, and abdominal pain. Although HAV does not cause chronic liver damage and typically resolves within 2-6 months, severe cases can lead to complications like fulminant hepatitis, myocarditis, and rare extrahepatic manifestations. Treatment is supportive, and recovery usually results in lifelong immunity. Case report: An 8-year-old female presented with a high-grade fever, jaundice, vomiting, and abdominal pain. She was admitted to the Pediatric ICU with bradycardia, abnormal lab results indicating acute viral hepatitis A, and suspected viral myocarditis. On the third day of admission (DOA), oxygen saturation dropped further to 77%. The patient was shifted to continuous positive airway pressure and was considered at risk of cardiogenic shock. Despite treatment, including a temporary pacemaker and inotropes, her condition worsened, leading to cardiogenic shock and death on the fourth day of admission. Conclusion: Acute viral hepatitis caused by the HAV can be complicated by development of complete heart block secondary to viral myocarditis and may necessitate the installation of a TPM and can also lead to death. Specialized pediatric cardiac care is necessary to timely diagnose the condition. Close monitoring of the deteriorating cardiac condition of the child is important to prevent death. It is important to timely consider cardiac complications of symptomatic HAV infections and consider early shifting of patients to Mechanical Circulatory Support. Keywords: Hepatitis A virus, hepatitis, myocarditis, pacemaker, pediatrics